THU0027 TREM-1 stimulation inhibits human osteoclastogenesis via down-regulation of M-CSF receptor expression. (23rd January 2014) - Lee, B.; Kim, T.-H.; Kwon, E.; Choi, S.J.; Lee, Y.H.; Sohn, J.; Song, G.G.; Ji, J.D.
Abstract : Background: Triggering receptor expressed on myeloid cells (TREMs) are a family of cell surface receptors that play important roles in innate and adaptive immunity. Among then, TREM-2 has been extensively studied in the osteoclast differentiation and the essential role of TREM-2 in human osteoclastogenesis has been well established. However, much less has been known about the role of TREM-1 in human osteoclast differentiation. Objectives: In this study, we investigated the role of TREM-1 in human osteoclast differentiation. Methods: In vitro osteoclastogenesis assays were performed using osteoclast precursors from normal peripheral blood. Gene expressions were analyzed using real-time PCR. Results: Consistent with previous reports, TREM-2 expression was strongly increased during generation of human osteoclast precursors (pOCs). In contrast, TREM-1 expression was significantly decreased during generation of human pOCs. Stimulation of TREM-1 using agonistic TREM-1 antibody resulted in a significant suppression of RANKL-induced osteoclastogenesis, as evidenced by diminished formation of TRAP+ multinucleated cells. In addition, TREM-1 stimulation strongly suppressed RANKL-induced expression of osteoclast-related genes such as cathepsin K, integrin β3 and NFATc1. TREM-1 stimulation also down-regulated gene expression and cell surface expression of M-CSF receptor that is essential for osteoclast differentiation and survival. Conclusions: In this study, we demonstrated that TREM-1 play a negative regulator in human osteoclast differentiation and our findings identify a new mechanism of negative regulation of osteoclastogenesis that play a role during inflammation. Disclosure of Interest: None Declared